Field reports of Iowa birds - Dinsmore, Stephen J.et al; Kent, Thomas H. (Thomas Hugh), 1934-et al (1985)
A list of birds sighted by Steve Dinsmore, compiled and printed out by Thomas Kent on December 1, 1985. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed